Climate Change in the Holocene and Early Neolithic Period (Journal of Misan Researches, 2024)
The Holocene era is the period of climate change from the cold and ice period to the moderate climate age, and its impact on the growth of plant and pastoral life and the recovery and abundance of water sources, in addition to the fertility of the land, which attracted the attention of the Paleolithic man, the era of hunting, moving and gathering that required effort, pain and fear from man. The climate changes in this era helped man strive to build a new life befitting his human status, socially, intellectually and artistically, and to enter a new era in his life, which is the Neolithic period, the period of agriculture, domestication, construction and stability. Perhaps the role of women in formulating some ideas, rituals and arts emerged, due to the available leisure, her overwhelming emotions, her intense fear, and her tireless efforts to provide food to help men, fearing for her family members, which helped the changing climate conditions to ensure the survival of larger numbers than in the previous period.